2017
DOI: 10.1103/physrevb.95.125417
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced topological phase transitions and strongly anisotropic magnetoresistance in bulk black phosphorus

Abstract: We report the anisotropic magneto-transport measurement on a non-compound band semiconductor black phosphorus (BP) with magnetic field B up to 16 Tesla applied in both perpendicular and parallel to electric current I under hydrostatic pressures. The BP undergoes a topological Lifshitz transition from band semiconductor to a zero-gap Dirac semimetal state, characterized by a weak localization-weak antilocaliation transition at low magnetic fields and the emergence of a nontrivial Berry Phase of π detected by Sd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…The lack of inversion symmetry in the A17 phase converts the 2D Dirac semimetal into a Weyl semimetal (20). A negative magnetoresistance (MR) for B // I, consistent with the chiral anomaly characteristic of a Weyl semimetal, has indeed been reported in a high-pressure transport study (7). The Weyl semimetal phase of BP shows no sign of superconductivity down to 45 mK (21).…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…The lack of inversion symmetry in the A17 phase converts the 2D Dirac semimetal into a Weyl semimetal (20). A negative magnetoresistance (MR) for B // I, consistent with the chiral anomaly characteristic of a Weyl semimetal, has indeed been reported in a high-pressure transport study (7). The Weyl semimetal phase of BP shows no sign of superconductivity down to 45 mK (21).…”
mentioning
confidence: 57%
“…and report an extremely large MR effect and quantum Shubnikovde Haas (SdH) oscillations under high pressure (7,10,16,(19)(20)(21)(22)(23)(24)(25)(26). Superconductivity in BP occurring right after the A7 phase is induced at P ≥ 5 GPa (27)(28)(29).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, topologically non-trivial semi-metallic properties have been discovered in the A17 structure at low pressure (i.e. a few GPa) [6][7][8][9] , which contributed to revitalizing the interest in this material. Under pressure, early studies showed that black phosphorus exhibits several phase transitions 1,2 .…”
Section: Introductionmentioning
confidence: 99%